Examining the manipulation of accounting and financial information: The case of Cameroonian companies - Moumeni, Yvonne (Eximia, 2023)
The question of the manipulation of accounting and financial information within companies is topical among accountancy debates. It is of peculiar interest and represents an accounting policy.issue. The aim of this study is to examine the reasons that spur the companies managers to manipulate financial statements reported to stakeholders. To address this concern, we made use of two analysing methods: firstly the exploratory method based on a 12 companies sample and secondly the quantitative method based on a 210 companies sample. The ordinal logistic regression helped processing the data. The results show that there are many motives that spur the managers to manipulate accounting and financial data. On the one hand, there are accounting choices and the involvement of the managers in producing them and on the other hand, there is institutional pressure.